Effect of Sodium-Glucose Co-transporter Protein 2 Inhibitors on Arrhythmia in Heart Failure Patients With or Without Type 2 Diabetes: A Meta-Analysis of Randomized Controlled Trials - Yin, Ziwei; Zheng, Huizhen; Guo, Zhihua (Frontiers in Cardiovascular Medicine, 2022)
Aim: Arrhythmic events such as atrial fibrillation (AF) are tightly associated with an increased risk of heart failure (HF). Previous studies have shown inconsistent results regarding the association between sodium-glucose co-transporter 2 inhibitors (SGLT2i) and the risk of arrhythmia. The purpose of this study was to investigate the association of SGLT2i treatment with arrhythmia outcomes in clinical trials of patients with HF. Methods: We searched Embase, PubMed, Web of Science, Medline, The Cochrane Library, and JAMA databases to identify appropriate randomized controlled trials (RCTs) of SGLT2i interventions. Primary outcomes included AF, atrial flutter (AFL), ventricular fibrillation (VF), ventricular tachycardia (VT), bradycardia, and cardiac arrest. A random-effects model was used for the meta-analysis of all outcomes. The risk of bias and quality of evidence was assessed by using the Cochrane tool and assessment framework. Results: Out of 1725 citations, 10 trials were included in this study, with follow-up from 4 weeks to 52 weeks for 10,416 participants (mean age 68.28 years; 7134 [68.49%] of participants were men). Compared with placebo, SGLT2i reduced the incidence of AF by 37% (ratio risk [RR] 0.63; 95% confidence interval [CI] 0.45-0.87; p < 0.05) and AF/AFL by 34% (RR 0.66; 95% CI 0.49-0.90; p < 0.05). Conclusions: SGLT2i reduces the risk of cardiac arrhythmias, particularly atrial fibrillation. Our study provides strong evidence for recommending the use of SGLT2i in patients with HF.